Lithium-organic sulfur battery composite electrode and preparation method and application thereof
By using a three-layer interlayer composite structure of a current collector, a lithium-organic sulfur dry electrode and an electrolyte reservoir in the lithium-organic sulfur battery, the liquid phase organic polysulfide is synthesized in situ by a mixture of organic sulfur and sulfur element, the poor wetting of the electrolyte caused by low load and increased electrode thickness in the prior art is solved, and the battery performance with high load and good cycle stability is achieved.
Patent Information
- Application Number
- CN202410645139.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-23
- Publication Date
- 2025-03-28
AI Technical Summary
The load of the existing lithium-organic sulfur battery cathode material is low, which is difficult to meet commercial needs. At the same time, the high load of the cathode leads to an increase in the electrode thickness, an increase in the ion/electron transmission distance, poor infiltration of the electrolyte, and slow reaction kinetics, which affects the reversible capacity and electrochemical performance of the battery.
Using a three-layer interlayer composite structure of a current collector, a lithium-organic sulfur dry electrode and an electrolyte reservoir, the lithium-organic sulfur dry electrode is prepared by solvent-free dry rolling technology. The active substance is a mixture of organic sulfur and sulfur element, and the liquid phase organic polysulfide is synthesized in situ during the electrochemical process.
While achieving high load active substances, it has good cycle stability and rate performance, improving the discharge capacity and energy density of the battery, and overcoming the problems of poor wetting properties of high load thick electrodes obtained by dry rolling technology and low Coulomb efficiency.
Smart Images

Figure HDA0004854593000000011 
Figure HDA0004854593000000012 
Figure HDA0004854593000000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium-organic sulfur battery positive electrode materials, and specifically relates to a lithium-organic sulfur battery composite electrode and a preparation method and application thereof. Background Art
[0002] With the popularity of portable electronic devices and electric vehicles, the demand for high energy storage devices has increased dramatically, and lithium-ion batteries have become a research hotspot. However, lithium-ion batteries are limited by their inherent capacity (<250mAh g -1 ) and metal resource limitations have led people to explore other high-capacity and high-energy-density electrode materials. Organic sulfur electrode materials have the advantages of diverse structures, low cost, cycle stability and high capacity, and are a promising organic electrode material. However, the loading capacity of organic sulfur electrodes is low, which makes it difficult to meet commercial needs.
[0003] Dry electrode technology is more suitable for manufacturing high-load positive electrodes, and dry rolling technology is used to manufacture high-load organic sulfur positive electrodes. However, since the high-load positive electrode will lead to an increase in the thickness of the electrode sheet, this will lead to a proportional increase in the ion / electron transmission distance, and multiple rolling will lead to a low porosity of the electrode, making it difficult for the electrolyte to contact the active material, and the electrolyte wettability is poor, which will lead to challenges such as slow reaction kinetics, dissolution and shuttling of active materials, reducing the reversible capacity and electrochemical performance of the battery. Good performance of thick electrodes can be achieved through a high electrolyte / sulfur ratio (>10μL / mg), but this method will lead to a decrease in energy density, which will dim the prospects. A Chinese patent (application number 201710769612.0) discloses a dual-current collector sulfur positive electrode and its preparation method and application in lithium-sulfur batteries. The dual-current collector sulfur positive electrode comprises a lower current collector, an intermediate active material layer and an upper current collector, wherein the intermediate active material layer is composed of an active material and a binder; the sulfur active material loading per unit area can be 1 to 16 mg cm -2 When the sulfur loading is too high, the battery cycle performance is reduced. -2 Within the range of 100 cycles, the capacity retention rate of the battery is above 90%; when the loading is greater than 7 mg cm -2 When the battery is loaded, the resistance increases, the specific capacity and cycle characteristics deteriorate, and the coulombic efficiency decreases. Although this invention can achieve high load, the load increase is limited, and the load exceeds 7 mg cm -2 It is not conducive to the electrochemical performance.
[0004] Therefore, there is an urgent need to produce a high-load and high-stability organic sulfur cathode to achieve high capacity and high stability of organic sulfur. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a lithium-organic sulfur battery composite electrode and a preparation method and application thereof, which has good cycle stability while loading active substances at a high loading capacity.
[0006] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0007] Provided is a lithium-organic sulfur battery composite electrode, which comprises a current collector, a lithium-organic sulfur dry electrode and an electrolyte storage in sequence, wherein:
[0008] The lithium-organic sulfur dry electrode is prepared by dry rolling technology of positive electrode active material, conductive agent and binder under solvent-free conditions; the positive electrode active material is a mixture of organic sulfur and sulfur element;
[0009] In the lithium-organic sulfur dry electrode, the single-side loading of the positive electrode active material is ≤44.6 mg cm -2 .
[0010] According to the above scheme, the lithium-organic sulfur dry electrode is prepared by mixing and grinding the positive electrode active material and the conductive agent, adding a binder, and then fibrillating the binder under the action of shear force to bind the powder into blocks, and then rolling to obtain the lithium-organic sulfur dry electrode.
[0011] According to the above scheme, in the lithium organic sulfur dry electrode, the single-sided loading amount of the positive electrode active material is ≤25mgcm -2 ; preferably 5 to 25 mg cm -2 More preferably, 8 to 25 mg cm -2 ; More preferably, 18 to 25 mg cm -2 .
[0012] According to the above scheme, the molar ratio of sulfur to organic sulfur is 1 to 4:1. Sulfur and organic sulfur can be used to synthesize polysulfur organic matter in situ through electrochemistry. For example, sulfur and diphenyl disulfide can be used to synthesize diphenyl tetrasulfide in situ at a molar ratio of 2:1; sulfur and 2,2'-bipyridyl disulfide can be used to synthesize 2,2'-bipyridyl trisulfide in situ at a molar ratio of 1:1.
[0013] According to the above scheme, the organic sulfur is 4,4'-thiodibenzenethiol (TBBT), dimethyl trisulfide, diphenyl disulfide, dipentylthiuram tetrasulfide or 2,2'-bipyridyl disulfide.
[0014] According to the above scheme, in the lithium organic sulfur dry electrode, the mass ratio of the positive electrode active material, the conductive agent, and the binder is 30-90:9-60:1-10.
[0015] According to the above scheme, the conductive agent is at least one of acetylene black, Ketjen black, carbon nanotubes, carbon nanofibers, graphene, and graphene oxide; preferably Ketjen black.
[0016] According to the above scheme, the binder is one or a combination of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE); preferably PTFE.
[0017] According to the above scheme, the current collector is one of carbon-coated aluminum foil, aluminum foil, aluminum mesh, titanium mesh and other metal foils, preferably aluminum mesh.
[0018] According to the above scheme, the electrolyte reservoir is a porous adsorption layer; specifically, a polymer with a porous structure, a ceramic coating material, an inorganic material, a carbon-based material or some functional polymers; preferably, a carbon-based material.
[0019] Provided is a method for preparing the above-mentioned lithium-organic sulfur battery composite electrode, comprising the following steps: rolling and compounding the lithium-organic sulfur dry electrode on a current collector, and then rolling an electrolyte reservoir on the lithium-organic sulfur dry electrode to obtain the lithium-organic sulfur battery composite electrode.
[0020] According to the above scheme, the preparation of the lithium-organic sulfur dry electrode includes the following steps:
[0021] The positive electrode active material and the conductive agent are mixed and ground, and then a binder is added. Then, under the action of shear force, the binder is fiberized and the powder is bonded into blocks. After rolling, a lithium-organic sulfur dry electrode is obtained.
[0022] Preferably, the grinding time is 20 to 25 minutes.
[0023] Provided is a lithium-organic sulfur battery, comprising the lithium-organic sulfur battery composite positive electrode.
[0024] According to the above scheme, the lithium-organic sulfur battery also includes a negative electrode and an electrolyte.
[0025] Preferably, the negative electrode is metallic lithium, and the electrolyte is a commercial lithium-sulfur electrolyte.
[0026] According to the above scheme, the lithium-organic sulfur battery is prepared and allowed to stand for 3-12 hours before use.
[0027] According to the above scheme, during the charging and discharging process of the lithium-organic sulfur battery, the elemental sulfur and organic sulfur in the composite positive electrode of the lithium-organic sulfur battery synthesize organic polysulfide in situ through electrochemistry.
[0028] Preferably, the in-situ electrochemical synthesis voltage range is 1-5V. Furthermore, the charge and discharge voltage range can be determined according to the required charge and discharge products of the active substance. Different charge and discharge voltages can determine the charge and discharge products of the battery and the electrochemical behavior of the battery.
[0029] The present invention provides a lithium-organic sulfur battery composite electrode, which is provided with a three-layer sandwich composite structure of a current collector, a lithium-organic sulfur dry electrode and an electrolyte storage, wherein the lithium-organic sulfur dry electrode is prepared by a solvent-free dry rolling technology, and a high load of electrode active substances is achieved, but the high-load thick electrode prepared by the dry method has the problem of poor wettability. On the one hand, the present invention adopts a three-layer sandwich composite structure of a current collector, a lithium-organic sulfur dry electrode and an electrolyte storage, and the electrolyte storage can intercept sufficient electrolyte to enhance the wettability of the electrolyte to the positive electrode; on the other hand, the active material of the lithium-organic sulfur dry electrode is a mixture of organic sulfur and sulfur element, and liquid phase organic polysulfide can be synthesized in situ during the electrochemical process, thereby increasing the contact area between the active material and the electrolyte during the cycle, accelerating the mass transfer process, and improving the utilization rate of the active material, bringing better wetting effect and cycle stability.
[0030] In addition, the present invention sandwiches a mixture of organic sulfur and sulfur element in the middle through a three-layer sandwich composite structure, electrochemically synthesizes liquid organic polysulfide in situ, and realizes the application of liquid organic polysulfide in the preparation of electrodes by dry rolling technology through a simple method, further improving the loading amount of active substances; at the same time, the in situ synthesis can be used and prepared at any time, the method is simple, the conditions are mild, the process is effectively reduced, raw materials are saved, and costs are reduced; and the electrochemical in situ synthesis has high synthesis efficiency, few by-products, and the obtained organic polysulfide has good repeatability, which is conducive to the consistency of electrochemical performance.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0032] 1. The present invention provides a lithium-organic sulfur battery composite electrode, which is provided with a three-layer sandwich composite structure of a current collector, a lithium-organic sulfur dry electrode and an electrolyte storage. At the same time, the active material of the lithium-organic sulfur dry electrode is a mixture of organic sulfur and sulfur element, which can synthesize liquid organic polysulfide in situ during the electrochemical process, realize the application of liquid organic polysulfide in the preparation of electrodes by dry rolling technology, and effectively make up for the poor wettability of high-load thick electrodes obtained by dry rolling technology, low and unstable coulombic efficiency, poor cycle stability and other problems; in the composite electrode obtained by the present invention, the active material loading is high (can reach ≤44.6mg cm -2 ), can improve the discharge capacity of the battery and increase the energy density; and while loading active substances at a high load, it also has good cycle stability and rate performance, which is conducive to commercial promotion and application.
[0033] 2. In the lithium-organic sulfur battery composite electrode obtained by the present invention, organic sulfur and sulfur element can react in situ during the charge and discharge process to generate liquid organic polysulfide, which can be used and prepared at any time. The method is simple, the conditions are mild, and the repeatability is good, which is conducive to the consistency of electrochemical performance.
[0034] 3. The present invention provides a method for preparing a lithium-organic sulfur battery composite electrode, which has a simple preparation process and can be produced on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used for explaining the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.
[0036] Figure 1 The figure is a flow chart of the preparation of a solvent-free lithium-organic sulfur composite electrode in an embodiment of the present invention.
[0037] Figure 2 The loading amount of Example 1 of the present invention is 17.1 mg cm -2 Cycling performance of the solvent-free electrode at 0.1C rate.
[0038] Figure 3 The loading amount in Example 1 of the present invention is 17.1 mg cm -2 Voltage-capacity first cycle distribution diagram of the solvent-free electrode at 0.1C rate.
[0039] Figure 4 This is a schematic diagram of the in-situ electrochemical synthesis of organic polysulfides from elemental sulfur and diphenyl disulfide DPDS, the active substances of the composite electrode obtained in Example 1 of the present invention.
[0040] Figure 5 The figure is a comparison of the cycle performance with and without the current collector in Example 1 of the present invention.
[0041] Figure 6 The figure shows the cycle performance comparison between the embodiment 1 of the present invention with and without the electrolyte reservoir.
[0042] Figure 7 The figure is a comparison of the cycle performances of different conductive agents used in Example 1 of the present invention.
[0043] Figure 8 The loading amount in Example 2 of the present invention is 20 mg cm -2 The cycling performance of the composite electrode at 0.1C rate.
[0044] Fig. 9 The loading amount in Example 2 of the present invention is 20 mg cm -2Voltage-capacity first cycle distribution diagram of the composite electrode at 0.1C rate.
[0045] Fig.10 This is a schematic diagram of the in-situ electrochemical synthesis of organic polysulfides from sulfur and 2,2'-DpyDs, the active substances of the composite electrode obtained in Example 2 of the present invention.
[0046] Fig.11 The loading amount in Comparative Example 1 of the present invention is 8 mg cm -2 The cycling performance of the composite electrode at 1C rate.
[0047] Fig.12 The loading amount in comparative example 1 of the present invention is 8 mg cm -2 Voltage-capacity first cycle distribution diagram of the composite electrode at 1C rate.
[0048] Fig.13 The loading amount in Comparative Example 2 of the present invention is 20 mg cm -2 The cycling performance of the composite electrode at 0.1C rate. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0050] Example 1
[0051] A specific preparation method for a lithium-organic sulfur battery composite electrode is provided. The preparation process is as follows Figure 1 As shown, the following steps are included:
[0052] Sulfur (S) and organic sulfur (diphenyl disulfide DPDS) were mixed in a molar ratio of 2:1 as an organic sulfur active material (named S-DPDS-21), and the organic sulfur active material and Ketjen black were preliminarily ground and mixed in a mass ratio of 79:20 to obtain a mixed powder. Then, the mixed powder and polytetrafluoroethylene binder were mixed in a mass ratio of 99:1. Finally, under the action of shear force, the polytetrafluoroethylene binder was fibrillated to bind the mixed powder into an electrode blank. The obtained electrode blank was rolled and cut to obtain a lithium organic sulfur dry electrode, in which the loading amount of the organic sulfur active material was 17.1 mg cm -2 .
[0053] The lithium-organic sulfur dry electrode is rolled onto an aluminum mesh, and then a porous carbon-based material layer is rolled onto the lithium-organic sulfur dry electrode to form a lithium-organic sulfur battery composite electrode having an aluminum mesh, a lithium-organic sulfur dry electrode, and a porous carbon-based material layer.
[0054] The battery was assembled, with the positive electrode being the lithium-organic sulfur battery composite electrode obtained above as the positive electrode, the negative electrode being metallic lithium, and the electrolyte being a commercial lithium sulfur electrolyte (1M LiTFSIDME:DOL=1:1+1%LiNO3). Specifically: 40 μl of electrolyte was dripped on the positive electrode side to fully wet the positive electrode sheet, and 20 μl of electrolyte was added on the negative electrode side. The button cell was assembled and left to stand for 12 hours to ensure that the composite electrode was fully wetted. The voltage was set in the range of 1.8-3V, and its electrochemical performance was tested.
[0055] like Figure 2 As shown, the loading capacity is 17.1 mg cm -2 The battery made of the solvent-free electrode has a cycle performance of 82.2% at a rate of 0.1C after 50 cycles. Figure 4 As shown, in situ electrochemical synthesis of diphenyl trisulfide DPTS and diphenyl tetrasulfide PTS was carried out during the charging process (the target product diphenyl tetrasulfide PTS has a theoretical specific capacity of 570 mAh g -1 ), the synthesized diphenyl tetrasulfide PTS is in liquid form, which increases the contact area with the electrolyte and improves the infiltration effect of the electrolyte. Figure 3 for Figure 2 The first cycle charge-discharge voltage curve and its voltage platform characteristics indirectly prove the successful synthesis of diphenyltetrasulfide PTS.
[0056] In order to explore whether the improvement measures made by the present application for the negative effects of the dry high-load thick electrode of organic sulfur are effective, based on the preparation of Example 1, we explored the type of conductive agent, the cycle performance with or without the preferred current collector and electrolyte storage, among which Figure 5-7 The differences in loading are due to normal errors in the preparation process. Figure 5 As shown in the figure, the effects of the presence or absence of current collector on the performance of dry electrodes are shown. It can be clearly observed that due to the improvement of electrolyte wettability, the electrode with titanium mesh current collector has higher discharge capacity and cycle stability than the electrode without current collector. Figure 6 As shown in the figure, the performance of the porous electrolyte reservoir in the dry thick electrode is significantly optimized, the initial capacity is improved, the active substances and polysulfides are adsorbed, and the cycle stability is good. At the same time, due to the improved wettability of the electrode, the capacity of the electrode with the electrolyte reservoir is fully utilized. Figure 7As shown, the present application studies the influence of different conductive agents on the battery with respect to the electrode wettability problem of organic sulfur, and explores the influence of conductive agents on the performance of organic sulfur in conductive carbon black (Super P), acetylene black (AB), Ketjen black (KB), and multi-walled carbon nanotubes (MWCNTs). Among acetylene black, conductive carbon black, multi-walled carbon nanotubes and Ketjen black, when the conductive agent is Ketjen black, a higher initial capacity can be released, the cycle stability is better, and the electrochemical performance is the best.
[0057] Example 2
[0058] A specific preparation method of a lithium-organic sulfur battery composite electrode is provided, comprising the following steps:
[0059] Sulfur (S) and organic sulfur (2,2'-DpyDs) were mixed in a molar ratio of 1:1 as an organic sulfur active material (named S-2,2'-DpyDS-11), and the organic sulfur active material and Ketjen black were preliminarily mixed in a mass ratio of 84:15 to obtain a mixed powder. Then, the mixed powder and polytetrafluoroethylene binder were mixed in a mass ratio of 99:1. Finally, under the action of shear force, the polytetrafluoroethylene binder was fibrillated to bind the mixed powder into an electrode blank. The obtained electrode blank was rolled and cut to obtain a lithium organic sulfur dry electrode, in which the loading amount of the organic sulfur active material was 20 mg cm -2 .
[0060] The lithium-organic sulfur dry electrode is rolled onto an aluminum mesh, and then a porous carbon-based material layer is rolled onto the lithium-organic sulfur dry electrode to form a lithium-organic sulfur battery composite electrode having an aluminum mesh, a lithium-organic sulfur dry electrode, and a porous carbon-based material layer.
[0061] The battery was assembled, with the positive electrode being the lithium-organic sulfur battery composite electrode obtained above as the positive electrode, the negative electrode being metallic lithium, and the electrolyte being a commercial lithium sulfur electrolyte (1M LiTFSIDME:DOL=1:1+1%LiNO3). Specifically: 40 μl of electrolyte was dripped on the positive electrode side to fully wet the positive electrode sheet, and 20 μl of electrolyte was added on the negative electrode side. The button cell was assembled and left to stand for 12 hours to ensure that the composite electrode was fully wetted. The voltage was set in the range of 1.8-3V, and its electrochemical performance was tested.
[0062] like Figure 8 As shown, the loading capacity is 20 mg cm -2 The cycling performance of the composite electrode at a rate of 0.1C shows that the capacity retention rate is 90.4% after 50 cycles.
[0063] Fig. 9 The corresponding voltage-capacity first-cycle distribution diagram indirectly proves the feasibility of the in situ electrochemical synthesis strategy of 2,2'-pyridine trisulfide.
[0064] like Fig.10 As shown in the figure, 2,2'-pyridine trisulfide (Py2S3) was synthesized in situ during the charging process, with a theoretical specific capacity of 425.4 mAh g -1 ).
[0065] Comparative Example
[0066] Provided is a method for preparing a lithium-organic sulfur battery composite electrode using a solid organic sulfur substance by a dry process.
[0067] (1) The organic sulfur active substance is dipentylthiuram tetrasulfide (PMTT, with a theoretical specific capacity of 418 mAh g -1 ), the organic sulfur active material and Ketjen black are preliminarily mixed in a mass ratio of 90:9 to obtain a mixed powder. The mixed powder and the binder are mixed in a mass ratio of 99:1, and finally, under the action of shear force, the polytetrafluoroethylene binder is fibrillated to bind the mixed powder into an electrode blank, and the obtained electrode blank is rolled and cut to obtain a lithium-organic sulfur dry electrode, wherein the loading amount of the organic sulfur active material is 8 mg cm -2 .
[0068] The lithium-organic sulfur dry electrode is rolled onto an aluminum mesh, and then a porous carbon-based material layer is rolled onto the lithium-organic sulfur dry electrode to form a lithium-organic sulfur battery composite electrode having an aluminum mesh, a lithium-organic sulfur dry electrode, and a porous carbon-based material layer.
[0069] The battery was assembled, with the positive electrode being the lithium-organic sulfur battery composite electrode obtained above as the positive electrode, the negative electrode being metallic lithium, and the electrolyte being a commercial lithium sulfur electrolyte (1M LiTFSIDME:DOL=1:1+1%LiNO3). Specifically: 40 μl of electrolyte was dripped on the positive electrode side to fully wet the positive electrode sheet, and 20 μl of electrolyte was added on the negative electrode side. The button cell was assembled and left to stand for 12 hours to ensure that the composite electrode was fully wetted. The voltage was set in the range of 1.8-3V, and its electrochemical performance was tested.
[0070] like Fig.11 As shown, the loading capacity is 8 mg cm -2 The cycling performance of the composite electrode at 1C rate is 81.6% after 80 cycles.
[0071] Fig.12 The corresponding voltage-capacity first cycle distribution diagram is shown in the figure. The three voltage platforms are the charge and discharge characteristic voltage curves of PMTT.
[0072] (2) The specific steps are the same as those of comparative example (1), except that the loading amount of active substance is 20 mg cm -2 .
[0073] Fig.13 The loading amount in comparative example (2) is 20 mg cm -2 The cycling performance of the composite electrode at a rate of 0.1C is 77.1% after 50 cycles, and the cycling stability is not as good as that of Examples 1 and 2. At the same time, the coulombic efficiency is low and unstable, which leads to a shortened battery life and potential safety hazards. Only organic sulfur is used as the active material. -2 When the electrode is thick, and the active material is solid, the electrolyte wettability is poor and the dynamic performance is poor.
[0074] The above results are analyzed to show that the lithium-organic sulfur battery composite electrode provided by the present invention has a three-layer sandwich composite structure of a current collector, a lithium-organic sulfur dry electrode and an electrolyte storage, and the active material of the lithium-organic sulfur dry electrode is a mixture of organic sulfur and sulfur element, which is used to in situ synthesize liquid organic polysulfide in the electrochemical process, thereby realizing the application of liquid organic polysulfide in the preparation of electrodes by dry rolling technology, effectively overcoming the problems of poor wettability, low and unstable coulombic efficiency, and poor cycle stability of high-load thick electrodes obtained by dry rolling technology; the loading amount is significantly increased, the discharge capacity of the battery is increased, and while the active material is loaded at a high loading amount, it also has good cycle stability and rate performance.
[0075] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A lithium-organic sulfur battery composite electrode, characterized in that: The invention comprises a current collector, a lithium-organic sulfur dry electrode and an electrolyte storage device in sequence, wherein: The lithium-organic sulfur dry electrode is prepared by dry rolling technology of positive electrode active material, conductive agent and binder under solvent-free conditions; the positive electrode active material is a mixture of organic sulfur and sulfur element; In the lithium-organic sulfur dry electrode, the single-side loading of the positive electrode active material is ≤44.6 mg cm -2 .
2. The composite electrode according to claim 1, characterized in that The lithium-organic sulfur dry electrode is prepared by mixing and grinding a positive electrode active material and a conductive agent, adding a binder, and then fibrillating the binder under the action of shear force to bind the powder into a block, and then rolling to obtain the lithium-organic sulfur dry electrode.
3. The composite electrode according to claim 1, characterized in that The molar ratio of elemental sulfur to organic sulfur is 1 to 4:
1.
4. The composite electrode according to claim 1, characterized in that: The organic sulfur is 4,4'-thiodibenzenethiol, dimethyl trisulfide, diphenyl disulfide, diamylthiuram tetrasulfide or 2,2'-bipyridyl disulfide.
5. The composite electrode according to claim 1, characterized in that: The conductive agent is at least one of acetylene black, Ketjen black, carbon nanotubes, carbon nanofibers, graphene, and graphene oxide; the binder is one or a combination of polyvinylidene fluoride and polytetrafluoroethylene; the current collector is one of carbon-coated aluminum foil, aluminum foil, aluminum mesh, titanium mesh or other metal foils; the electrolyte reservoir is a polymer with a porous structure, a ceramic coating material, an inorganic material, a carbon-based material or some functional polymers.
6. The composite electrode according to claim 1, characterized in that: In the lithium-organic sulfur dry electrode, the single-side loading amount of the positive electrode active material is 5 to 25 mg cm -2 .
7. The composite electrode according to claim 1, characterized in that: In the lithium organic sulfur dry electrode, the mass ratio of the positive electrode active material, the conductive agent and the binder is 30-90:9-60:1-10.
8. A method for preparing a lithium-organic sulfur battery composite electrode according to any one of claims 1 to 7, characterized in that: The following steps are involved: The lithium-organic sulfur dry electrode is rolled and composited on the current collector, and then the electrolyte reservoir is rolled and pressed on the lithium-organic sulfur dry electrode to obtain a lithium-organic sulfur battery composite electrode.
9. The preparation method according to claim 8, characterized in that: The positive electrode active material and the conductive agent are mixed and ground, and then a binder is added. Then, under the action of shear force, the binder is fiberized and the powder is bonded into blocks. After rolling, a lithium-organic sulfur dry electrode is obtained.
10. A lithium-organic sulfur battery, characterized in that: The invention comprises the lithium-organic sulfur battery composite positive electrode as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Dual-current collector sulfur positive electrode, preparation method thereof and application thereof in lithium-sulfur battery
CN107565097A